ICT in the real world publishing a magazine - Gough, Catherine; Video Education Australasia (Australia : Video Education Australasia, 2010)
'Maintaining and developing new and existing technologies requires the use of solid problem solving techniques. In this program, we explain the system of problem solving methodologies that have been devised to assist people in creating technological solutions. Presented using real-life examples with an emphasis on fulfilling customer needs, this program clearly highlights the advantages of following a logical approach when solving a problem. From designing, developing and testing, through to implementation, evaluation, and reporting on the outcomes, this program will ensure viewers approach problem solving using a proven strategic method.'--VEA website
Executive producer, Simon Garner ; director of photography, Ben Milward Bason, Jared Marshall
Voice over: Paul Seidel
DVD format
Keywords: Information technology; Desktop publishing